The Digital Black Atlantic - Risam, Roopika; Josephs, Kelly Baker (University of Minnesota Press, 2021)
Exploring the intersections of digital humanities and African diaspora studies How can scholars use digital tools to better understand the African diaspora across time, space, and disciplines? And how can African diaspora studies inform the practices of digital humanities? These questions are at the heart of this timely collection of essays about the relationship between digital humanities and Black Atlantic studies, offering critical insights into race, migration, media, and scholarly knowledge production.The Digital Black Atlantic spans the African diaspora's range-from Africa to North America, Europe, and the Caribbean-while its essayists span academic fields-from history and literary studies to musicology, game studies, and library and information studies. This transnational and interdisciplinary breadth is complemented by essays that focus on specific sites and digital humanities projects throughout the Black Atlantic. Covering key debates, The Digital Black Atlantic asks theoretical and practical questions about the ways that researchers and teachers of the African diaspora negotiate digital methods to explore a broad range of cultural forms including social media, open access libraries, digital music production, and video games. The volume further highlights contributions of African diaspora studies to digital humanities, such as politics and representation, power and authorship, the ephemerality of memory, and the vestiges of colonialist ideologies. Grounded in contemporary theory and praxis, The Digital Black Atlantic puts the digital humanities into conversation with African diaspora studies in crucial ways that advance both. Contributors: Alexandrina Agloro, Arizona State U; Abdul Alkalimat; Suzan Alteri, U of Florida; Paul Barrett, U of Guelph; Sayan Bhattacharyya, Singapore U of Technology and Design; Agata Błoch, Institute of History of Polish Academy of Sciences; Michał Bojanowski, Kozminski U; Sonya Donaldson, New Jersey City U; Anne Donlon; Laurent Dubois, Duke U; Amy E. Earhart, Texas A&M U; Schuyler Esprit, U of the West Indies; Demival Vasques Filho, U of Auckland, New Zealand; David Kirkland Garner; Alex Gil, Columbia U; Kaiama L. Glover, Barnard College, Columbia U; D. Fox Harrell, MIT; Hélène Huet, U of Florida; Mary Caton Lingold, Virginia Commonwealth U; Angel David Nieves, San Diego State U; Danielle Olson, MIT; Tunde Opeibi (Ope-Davies), U of Lagos, Nigeria; Jamila Moore Pewu, California State U, Fullerton; Anne Rice, Lehman College, CUNY; Sercan Şengün, Northeastern U; Janneken Smucker, West Chester U; Laurie N.Taylor, U of Florida; Toniesha L. Taylor, Texas Southern U.